Sehat Sahulat Program; A perspective from beneficiaries of Faisalabad, Pakistan: Sehat Sahulat Program - Tehreem, Rimsha; Mahmood, Humaira; Khan, Jawaria; Habib, Muhammad Farrukh; Zulfiqar, Rubab; Hassan, Uzma; Nadeem, Zainab; Bano, Bibi Razia; Shaheen, Dur E Yaqta; Diba, Farah (Pakistan Journal of Health Sciences, 2023)
Central Bureau of Health Intelligence denotes to offer financial protection through раying illness соst, and quality services of Heаlthсаre. The Sehat Sahulat рrоgrаm is one of the best рrоgrаm that has been started by the Раkistаn government, launched in 2015 to work on health for all. Objective: To assess the responsiveness of Sehat Sahulat Program. Methods: A descriptive cross-sectional study conducted in Faisalabad’s hospitals from Feb to Sep 2022. A validated structured questionnaire was administered to assess responsiveness of participants. A total of 307 participants aged 12 to 90 years fulfilling the inclusion criteria were recruited. Results: 307 participants were included in the study in which 139 (45.3%) were males and 168 (54.7%) were female. 140 (45.6%) of the total participants were rural, while 167 (54.4%) were urban. Of these, 26.6% expressed satisfaction with the services, and 48.7% thought they were good. Conclusions: It concluded that the greater part of individuals was satisfy with the services of Sehat Insaf card. It was found that age, residence, education, occupation and monthly income has shown statistically significant association with responsiveness. From eight domains of responsiveness quality of basic amenities was most important for beneficiaries then prompt attention and communication. In spite of satisfaction of beneficiaries, there is still a need for enhanced performance and fulfil their needs